Visualisasi Pemetaan Penyebaran Gempa Bumi Di Indonesia - Krisetianto, Wijaya Yoga; Mailoa, Evangs (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Earthquakes are natural disasters that can have devastating impacts on society. Indonesia needs education about areas that often experience natural disasters. This research was conducted to produce a visualization dashboard regarding mapping of earthquake areas in Indonesia, by applying the Business Intelligence method. This research resulted in the areas with the most earthquakes being the Minahasa Peninsula with 9,408 events with an average of 3.3 Mg, the island of Java with 6,772 events with an average of 3.4 Mg and North Sumatra with 5,920 events with an average of 3.3 Mg.